The Eyewitness Texture of Conflict: Contributions of Amateur Videos in News Coverage of the Arab Spring (Global Media Journal - German Edition, 2018)
Our paper uses the events of the Arab Spring to examine amateur videos as a discourse of conflict produced by untrained and unpaid individuals, often at great personal risk, and which is taken up by, and incorporated into, news outcomes by professional news networks. The different semiotic elements comprising amateur images used in news coverage create what we call an “eye-witness texture” that reflects not only the generally low quality technologies in use and non-professional camera skills, but the sensibilities of a public desire for proximity and immediacy, which is sometimes utilised by news organisations as a means to authenticate their coverage with affective and narrative features. The corpus of our study includes the amateur footage used in news coverage of Tunisia, Egypt and Libya during the first 100 days of the Arab Spring uprisings (December 17th 2010 to March 31st2011) by France 24 and the Canadian Broadcasting Corporation (CBC). Our paper uses a multipronged discourse analysis to reveal a range of priorities at work in the selection and use of amateur images. We notice that the inclusion of the eyewitness textures of amateur produced images in some cases implied meanings that tied news narratives to larger and largely ideological forms of discursive significance.
Keywords: user generated content; amateur produced images; Arab Spring; eyewitness textures